Propriedades estruturais e vibracionais de carbonatos fosfatos isoestruturados (Sidorenkitas) - Amaral, Ian Rodrigues do (2017)
Sidorenkite type isostructured carbonophosphates are the state-of-the-art cathode materials for modern Sodium-ion batteries. The layered structure with monoclinic symmetry offer a unique opportunity to exploit periodic sites in their structures to make possible the insertion and extraction of sodium ions at the cathode, which are the main source of the battery´s electromotive force. Making use of one of the most abundant element in the earth's crust, these devices are a great promise to replace the already widespread lithium-ion battery. However, the ideal cathode that produces the best performance, regarding high energy density and chemical stability is still being developed. Raman spectroscopy remains as one of the best method to characterize the properties of these compounds, having the great advantage of being highly sensitive to short-range environment of oxygen coordination around the transition metals, phosphorus and carbon atoms. Here, Raman spectroscopic analysis of a set of Na3MCO3PO4 (M = Mn, Fe, Co e Ni) carbonophosphates, obtained by hydrothermal synthesis in microwave at 210 ° C for 30 minutes was, performed. The insertion success of various metals in MO6 octahedra, with diferent ionic radii, produces a unit cell volume change in the crystal lattice, thus modifying the equilibrium distance of the whole structure interatomic bonds, leading to substantial shifting in the normal modes wavenumbers. Raman spectroscopy proved, therefore, to produce essential information for a reliable characterization of carbonophosphates, evidencing structural and chemical properties essential for developing an efficient and comercially viable material for these novel sodium batteries.